Prevalence of Hypernatremic Dehydration in Breast Fed Neonates: A Retrospective Study in a Tertiary Care Hospital - Ritu Agarwal; Ram Pal Singh Tomar; Ashish Kumar Gupta; Niranjan Sahoo (JCDR Research and Publications Pvt. Ltd., 2020)
Introduction: Neonatal Hypernatremic Dehydration (NHD) is a common occurrence in neonates. Important causes include inadequate breastfeeding, high content of sodium in breast milk, improper preparation of infant formula feeds, diarrhoea, vomiting and rarer causes such as Diabetes insipidus. Hypernatremia carries a high morbidity and mortality and therefore it is important to address the aetiological factors to prevent complications. Aim: To investigate the incidence of NHD, maternal and neonatal risk factors contributing to this problem along with its presenting symptoms and outcome after management. Materials and Methods: This was a retrospective study done in a tertiary centre over a five-year period, where all neonates admitted in Neonatal Intensive Care Unit (NICU) with serum sodium >145 mmol/l were included in the study. Neonatal data and maternal data were noted. Initiation and frequency, technique and any problems of breastfeeding were recorded. Management of hypernatremic dehydration was done as per the standard unit protocol. The results were plotted in MS Excel and analysed using SPSS 22 (Chicago, IL USA). Results were expressed in mean and SD in tables and compared using the Fisher's-extract test. Results: A total of 68 mothers-neonate dyads were included in the study. The mean day of presentation by the neonates was day 8 of life (SD 3.5). Moderate and severe hypernatremia were noted in 23 (33.2%) and 11 (16.8%) cases with total mortality in 3 cases. Factors that positively correlated with severe disease were primigravida mothers, latching difficulties, breast related problems, feeds less than 6 times/day, severe weight loss (>10%) and decreased urine frequency (<4/day). Conclusion: Inadequate breast feeding was associated with hypernatremic dehydration hence it is important to take care of breast problems starting from antenatal checkups along with proper education of mothers on breast feeding with advice for early follow-up in baby clinic to detect early breast feeding issues so as to take early corrective steps.